INTEGRATION OF RUQYAH SYAR'IYYAH AS A MENTAL-SPIRITUAL SHIELD IN FACING THE CHALLENGES OF EDUCATION IN THE SOCIAL MEDIA ERA - Mukmin Mukmin; Rizki Akmalia (Prodi PAI Sekolah Tinggi Agama Islam Serdang Lubuk Pakam, 2026)
The social media era presents complex educational challenges, ranging from moral degradation and digital addiction to mental health issues such as anxiety and depression among students. This article aims to examine the role of Ruqyah Syar’iyyah not merely as a metaphysical healing method, but as an integrative instrument in character education. Utilizing literature review and observations of digital phenomena, the study's findings indicate that the internalization of Ruqyah Syar’iyyah values-specifically Tauhid (monotheism) and Tazkiyatun Nafs (purification of the soul) can strengthen students spiritual resilience against the negative impacts of social media, such as cyberbullying, FOMO (fear of missing out), and exposure to destructive content. This dissertation concludes that ruqyah syar'iyyah as part of spiritual education based on the Qur'an provides benefits for the process of fostering self-integrity, which is the aim of the Qur'an in providing educational and health contributions to every human being in dealing with problems that include aspects jismiyah (physical), nafsiah (psychic), ruhiyah (spiritual). The usefulness of ruqyah syar'iyyah as self-development and producing spiritual education based on the Koran which includes all of these elements, so that it can form a human person who has morals and integrity and is beneficial to fellow humans.